Tungsten coatings under fusion relevant heat loads - Thomser, C.; Linke, J.; Matthews, G.; Riccardo, V.; Schmidt, A.; Vasechko, V. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Components for first wall applications in future nuclear fusion devices like ITER or DEMO need to fulfill special requirements. Especially transient thermal loads like Edge Localized Modes (ELMs) have a severe impact on the material damage. Tungsten coatings are being assessed for use instead of bulk tungsten. In order to quantify their material degradation, tungsten coatings on a fiber-reinforced graphite substrate were exposed to repeated short fusion relevant thermal pulses in an electron beam material test facility JUDITH 1 (Juelich Divertor Test Facility in Hot Cells).